Rectification and revival of muslim world - Azram, Mohammad (IIUM Press, 2011)
The present doldrums position and state of decadence, internal differences, external aggression (geographical and ideological), lack of self-confidence and dependence, illiteracy, political instability, economic disaster, lack of knowledge and wisdom, back benchers in science and technology, education, medicine, trade and business, banking system and defensive incapability of Muslim Ummah prompted me to write this article. Although most of the Muslim nations got their independence because of their dedicated struggle and historic events and incidents but the old masters remained active for a remote control over the Muslim Ummah. Their intellectuals and scholars, individually as well as collectively, have propagated and advised their leadership, the tactics and approaches by which Muslim Ummah can again be enslaved. Writings of S.P. Huntington and F. Fukuyama are clear examples. They are actively gearing the international institutions so cleverly that Muslim Ummah does not even realize their ill motives and objectives. They brought their leadership in a confronting position with Muslim Ummah and hence threatening the world peace. This situation prompted us to look at our principal sources of inspiration, which are, the Qur‟an, Sunnah of the Prophet (SAW), and examples of the “enlightened Caliphs” and see if we could work out a seminal guidelines for our rectification and revival. We have gathered together some of these impressions; these are all tentative, nothing final about them, but these are here nonetheless.